PRR7 is a transmembrane adaptor protein expressed in activated T cells involved in regulation of T cell receptor signaling and apoptosis - Hrdinka, Matous; Dráber, Peter; Stepánek, Ondrej; Ormsby, Tereza; Otáhal, Pavel; Angelisová, Pavla; Brdicka, Tomás; Paces, Jan; Horejsí, Václav; Drbal, Karel (The Journal of biological chemistry, 2011)
Transmembrane adaptor proteins (TRAPs) are important organizers and regulators of immunoreceptor-mediated signaling. A bioinformatic search revealed several potential novel TRAPs, including a highly conserved protein, proline rich 7 (PRR7), previously described as a component of the PSD-95/N-methyl-d-aspartate receptor protein complex in postsynaptic densities (PSD) of rat neurons. Our data demonstrate that PRR7 is weakly expressed in other tissues but is readily up-regulated in activated human peripheral blood lymphocytes. Transient overexpression of PRR7 in Jurkat T cell line led to gradual apoptotic death dependent on the WW domain binding motif surrounding Tyr-166 in the intracellular part of PRR7. To circumvent the pro-apoptotic effect of PRR7, we generated Jurkat clones with inducible expression of PRR7 (J-iPRR7). In these cells acute induction of PRR7 expression had a dual effect. It resulted in up-regulation of the transcription factor c-Jun and the activation marker CD69 as well as enhanced production of IL-2 after phorbol 12-myristate 13-acetate (PMA) and ionomycin treatment. On the other hand, expression of PRR7 inhibited general tyrosine phosphorylation and calcium influx after T cell receptor cross-linking by antibodies. Moreover, we found PRR7 constitutively tyrosine-phosphorylated and associated with Src. Collectively, these data indicate that PRR7 is a potential regulator of signaling and apoptosis in activated T cells.
Keywords: vápníková signalizace; Animals; apoptóza; Receptors, Antigen, T-Cell; Protein Structure, Tertiary; Jurkat buňky; Adaptor Proteins, Signal Transducing; HEK293 Cells; CD antigeny; ionofory; Amino Acid Motifs; Apoptosis; Lectins, C-Type; adaptorové proteiny signální transdukční; interleukin-2; U937 Cells; Antigens, Differentiation, T-Lymphocyte; Caco-2 buňky; terciární struktura proteinů; lidé; ionomycin; lektiny typu C; protoonkogenní proteiny c-jun; Interleukin-2; Carcinogens; Ionomycin; T-lymfocyty; HEK293 buňky; Tetradecanoylphorbol Acetate; receptory antigenů T-buněk; Antigens, CD; regulace genové exprese; fosforylace; karcinogeny; Calcium Signaling; krysa rodu Rattus; diferenciační antigeny T-lymfocytů; Proto-Oncogene Proteins c-jun; U937 buňky; tetradekanoylforbolacetát; Gene Expression Regulation; zvířata; Ionophores; Jurkat Cells; T-Lymphocytes; Caco-2 Cells; aminokyselinové motivy; Rats; Phosphorylation; Humans